Barriers and facilitators to the implementation of workplace health promotion programs: Employers' perceptions - Campmans, Jennifer M. D.; Smit, Denise J. M.; van Oostrom, Sandra H.; Engels, Josephine A.; Proper, Karin I. (Frontiers in Public Health, 2023)
Background: Workplace health promotion programs (WHPPs) can benefit the lifestyle and health of employees. However, not all WHPPs have been successful in their implementation and thus effectiveness. This study aimed to identify the barriers and facilitators to implementing an integrated WHPP, which targets multiple lifestyle factors at different levels (individual and organizational), from an employers’ perspective. Methods: Data were collected by two online focus groups among 18 representatives of eight different organizations. Data from the focus groups discussions were transcribed verbatim and analyzed using thematic analysis. Data was coded both inductively and deductively, using the Consolidated Framework for Implementation Research (CFIR) consisting of five domains, i.e., 1) Intervention Characteristics, 2) Outer Setting, 3) Inner Setting, 4) Characteristics of Individuals, and 5) Process. Ratings were performed to indicate the positive or negative influence and strength of a construct regarding the implementation of WHPPs. Results: Barriers and facilitators in all domains of the CFIR were found. Regarding characteristics of the WHPP, complexity and costs hindered implementation, while high adaptability facilitated implementation. An organization that met the needs of employees (outer setting) facilitated implementation. Available resources, access to knowledge, leadership involvement, and continuity of communication were facilitators within the inner setting. Barriers were different approaches to implementation within one organization and the perceived interference with employees’ lives. For the implementation process, involvement of key stakeholders including employees were identified as important barriers and facilitators. Conclusion: Various barriers and facilitators in different domains play a role in the implementation of integrated WHPPs according to employers. Strategies that tackle the identified barriers and incorporate the facilitators will likely contribute to a successful implementation of integrated WHPPs.